Routine blood analysis greatly reduces the false-negative rate of RT-PCR testing for Covid-19. - Ferrari, Davide; Sabetta, Eleonora; Ceriotti, Daniele; Motta, Andrea; Strollo, Marta; Banfi, Giuseppe; Locatelli, Massimo (Acta Biomedica Atenei Parmensis, 2020)
Background: The COVID-19 outbreak is now a pandemic disease reaching as much as 210 countries worldwide with more than 2.5 million infected people and nearly 200.000 deaths. Amplification of viral RNA by RT-PCR represents the gold standard for confirmation of infection, yet it showed false-negative rates as large as 15-20% which may jeopardize the effect of the restrictive measures taken by governments. We previously showed that several hematological parameters were significantly different between COVID-19 positive and negative patients. Among them aspartate aminotransferase and lactate dehydrogenase had predictive values as large as 90%. Thus a combination of RT-PCR and blood tests could reduce the false-negative rate of the genetic test. Methods: We retrospectively analyzed 24 patients showing multiple and inconsistent RT-PCR, test during their first hospitalization period, and compared the genetic tests results with their AST and LDH levels. Results: We showed that when considering the hematological parameters, the RT-PCR false-negative rates were reduced by almost 4-fold. Conclusions: The study represents a preliminary work aiming at the development of strategies that, by combining RT-PCR tests with routine blood tests, will lower or even abolish the rate of RT-PCR false-negative results and thus will identify, with high accuracy, patients infected by COVID-19.